KARAKTERISTIK ORGANOLEPTIK, SIFAT KIMIA DAN AKTIVITAS ANTIOKSIDAN TEH FORMULASI DAUN KAKAO DAN KAYU MANIS - Sadimantara, Muhammad Syukri; asranudin, asranudin; Sadimantara, Fahria Nadiryati; Sakir, Sakir; suwarjoyowirayatno, suwarjoyowirayatno (Jurnal Sains dan Teknologi Pangan, 2018)
ABSTRACTThe aims of this study was to determine the effect of cocoa and cinnamon leaf formulations onorganoleptic assessment, chemical properties and antioxidant activity of cocoa leaves tea. This studyused a Completely Randomized Design (CRD), consisting of 5 types of cocoa and cinnamon leaveformulation namely 100% of cocoa leaves: 0% of cinnamon (KM0), 95% of cocoa leaves: 5% ocinnamon (KM1), 90% of leaf cacao: 10% of cinnamon (KM2), 85% of cocoa leaves: 15% of cinnamo(KM3) and 80% of cocoa leaves: 20% of cinnamon (KM4). The formulations of cocoa and cinnamoleaves had significant effect (p <0.05) on color and taste organoleptic tests, but was not significantleffect on aroma parameters. Based on organoleptic assessment, cocoa leaves tea can be accepteby panelists. Moisture content, pH, and antioxidant activity of selected sample were 3.96%, 5.12-6.2and 39.55%, respectively. Based on these results, cocoa leaves tea with the addition of cinnamon canmeet the standard.Keywords: Cocoa Leaf Tea, Cinnamon, Organoleptic, Antioxidant activities.